Calibration, validation and automation of subsurface drip irrigation system using Arduino microcontroller - Ascencios, David (2020)
Current technological developments provide useful and easy-to-apply tools in automated management of irrigation systems. Automation has the main advantages of increasing the saving of resources such as investment, time and labor as well as improving the management of water resources. The research methodology was as follows: a) selection of the microcontroller, sensors, relay and communication module, b) calibration and validation of the sensors, c) integration of the programming codes, d) communication and development of the mobile application and e) irrigation system control and soil moisture monitoring. Analog and digital sensors were implemented to measure pressures, flow rates, soil moisture and water levels in the reservoir. The sensors were calibrated and validated, obtaining the R2 between 0.95-0.99 in the calibration indicating a high correlation between the physical and electrical variable; and obtaining R2 equal to 0.99 in the validation. The microcontroller received the information from the sensors and sent orders to the actuators through electrical signals, which activate a programming code, allowing the control of the irrigation system through relays, for switching the solenoid valves and solenoid pumps on and off. The management was done from a smartphone through an application connecting with the user via Bluetooth communication. The calibration and validation of the sensors allowed the development of integrated, reliable and safe automation for monitoring and control of the irrigation system, allows the increase in irrigation efficiency.